MRS ELM as Literacy Sponsorship and its Impacts on Nora Seed’s Self-Transformation in Matt Haig’s The Midnight Library - Nur Fitria Sholehah; Much. Koiri (CV. Ulil Albab Corp, 2026)
The present study examines the character of Mrs. Elm as a literacy sponsor in the character development of Nora Seed, particularly in relation to her conflict with despair and her internal struggle between life and death. Through the analysis of the relationship between these two characters, the study shows that literacy guidance by Mrs. Elm helps Nora transform from a person full of regret and despair into a more reflective individual who comes to terms with her life. In addition, the study investigates how Nora Seed’s self-transformation through the literacy process affects her self-perception, acceptance of life’s imperfections, and reinterpretation of past decisions that were previously considered failures. This study also contributes to literary studies by emphasizing the significance of literacy and the role of literacy sponsorship in shaping character development and psychological transformation in literary works.